ANALISA PERBANDINGAN BIAYA PERAWATAN KAPAL NELAYAN BERBAHAN KAYU DAN FIBER DI DAERAH UJUNGPANGKAH KABUPATEN GRESIK - Moh. Fahrudin Rifqi; Yulia Ayu Nastiti; Soffiana Agustin (Proceeding Maritime Business Management Conference, 2023)
This research contains an analysis of fishermen's boat maintenance starting from the availability of resources, repair methods, maintenance, costs and duration of the maintenance process. This is an issue that must be properly understood by boat owners and prospective fishermen. To determine the ideal type of wooden ship or FRP ship for use, the qualitative description method, which is included in the qualitative research category. To reveal actual events during research, the author's goal is to reveal events, phenomena, variables, situations and circumstances. This will allow us to present factual events as they unfold. The wooden boats and fiber boats studied on Jalan Ujungpangkah experienced different types of damage, so the repair and maintenance techniques or methods were not the same. On wooden ships, the damage that occurs is engine damage, hull damage, deck damage and keel damage. Whereas fiber boats include engine damage and propeller damage, the damage experienced by wooden and fiberglass boats is different and the repair techniques are also different. It can be seen from the calculation results that the cost of repairing a wooden boat is much more expensive than a fiberglass boat. Due to the strengthof the material, wooden boats have maintenance intervals of 5 years, more often than fiberglass boats, which is 20 to 12 years.